The Effect of the Implementation of Teacher Driving and Visionary Leadership on the Quality of Education in State Elementary Schools in Palembang City - Sulistyaningsih, Dewi Ayu; Harapan, Edi; Pahlawan, Pahlawan (Journal of English Language and Education, 2025)
This research is motivated by the importance of improving the quality of education which is influenced by the competence of teachers and the visionary leadership of school principals. The purpose of this study is to analyze the influence of Driving Teachers and Visionary Leadership on the quality of education in State Elementary Schools throughout Palembang City. The study used a quantitative approach with 92 respondents and 60 school principals. Data were obtained through observation, documentation, and questionnaires, with validity tests using the product moment formula, reliability using Cronbach's Alpha, and analysis prerequisite tests including normality, multicollinearity, heteroscedasticity, and autocorrelation tests. Data analysis was carried out by multiple regression. The results of the study showed that partially Driving Teachers had a positive effect of 44.5% and Visionary Leadership of 49.6%, while simultaneously both had a very strong positive influence on the quality of education, which was 95.4%. Thus, it can be concluded that Driving Teachers and Visionary Leadership have a significant contribution to improving the quality of education, especially if the two run synergistically.